JENIS PENGARUH KELOMPOK REFERENSI DALAM PEMBELIAN PRODUK FASHION BERMEREK TIRUAN PADA INDIVIDU DEWASA AWAL - Asti Ayu Wulan Permatasari; Purnomologi Ursila Nilamsari; Rayini Dahesihsari (Universitas Katolik Indonesia Atma Jaya, 2020)
The research aims to describe the references group influences on the consumption of counterfeit branded fashion products on early adulthood individuals. Reference groups refers to individuals or group that become references for individual to forming her/his values and attitudes. Since 2014, the most counterfeit product consumption is fashion, which results on economic loss up to 41 billion rupiahs. Previous study showed that the consumption of counterfeit products was not only influenced by the high price of the original products, but also by psychological aspects, such as motivation to be seen positively and accepted by the social groups. The research applies quantitative approach, using 30 items of references group influences questionnaire. The questionnaire measures three types of references group influences, including informational influence, utilitarian influence, and value expressive influence on early adult individuals who experiences to buy counterfeit branded fashion product. 155 respondents involved. Convenience sampling technique applied, with central tendency, friedman test and mann-whitney test being used for data analysis. The findings show that references group influences for buying counterfeit branded fashion product was in moderate level, with the most influences was informational influences compared to utilitarian and value expressive influences.